Ursodeoxycholic acid preparations in the complex treatment of non-alcoholic fatty liver disease and diabetes mellitus - U. A. Khalilova; V. V. Skvortsov (Лечащий Врач, 2023)
The article is devoted to the issues of the influence of diseases of the liver and biliary tract on carbohydrate metabolism and the treatment of these disorders with the help of ursodeoxycholic acid preparations. Approximately 75% of cases of non-alcoholic fatty liver disease occur on the background of obesity, dyslipidemia or type 2 diabetes mellitus. A strong pathophysiological interaction has now been demonstrated between non-alcoholic fatty liver disease and type 2 diabetes mellitus. One of the main pathogenetic causes of type 2 diabetes mellitus and non-alcoholic fatty liver disease is insulin resistance. At the same time, it is necessary to highlight the role of the intestinal microbiota and the epigenome in the manifestation and progression of non-alcoholic fatty liver disease. Therefore, treatment approachesmust be comprehensive. Diet therapy should be aimed at reducing the calorie content of food. However, in real clinical practice, clinicians face low adherence to appropriate and long-term dietary recommendations necessary for weight loss. The use of a low-calorie diet with a significant restriction of fats may increase the risk of gallstones. For the prevention of gallstone disease, ursodeoxycholic acid preparations can be recommended. The advantages of using ursodeoxycholic acid include a decrease in the severity of cytolysis and cholestasis syndromes; direct anti-apoptotic and immunomodulatory effect, antifibrotic effect; this is the only drug that has shown effectiveness in the treatment of severe cholestatic liver diseases; the drug can be used in childhood from birth, as well as in the II-III trimesters of pregnancy.